Damage and Degradation of Concrete under Coupling Action of Freeze-Thaw Cycle and Sulfate Attack - Wei Tian; Fangfang Gao (Advances in Materials Science and Engineering)
In this study, the mechanical behaviors, failure characteristics, and microstructure of concrete containing fly ash (FA) against combined freeze-thaw cycles and sulfate attack were studied compared with normal concrete, and the formation rates of corrosion products during coupling cycles were investigated. Results showed that, during the coupling action of freeze-thaw cycles and sodium sulfate solution, concrete containing 10% fly ash exposed in 5% sodium sulfate solution exhibited better freeze-thaw resistance. Meanwhile, the variation of compressive strength of concrete during the coupling cycles could be divided into two stages, including the strength enhancement stage and the strength reduction stage. Moreover, the proportion of micropores and capillary pores decreased obviously during combined freeze-thaw cycles and sulfate attack, and excessive concentration of sodium sulfate solution led to more macropores after high-frequency freeze-thaw cycles.